2019
DOI: 10.1002/ppul.24521
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in cystic fibrosis: From the past to the present and into the future

Abstract: Nutritional management is an integral part of multidisciplinary care for persons with cystic fibrosis. This review will look at how nutrition care has evolved over time. In addition, we will look at how some newer therapies impact nutrition care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 107 publications
0
24
0
7
Order By: Relevance
“…13 Significant associations were identified between nutritional status and PFTs in some studies. 12 In a multicenter study conducted by Zemel et al,14 z-scores of weight and height of people with CF were positively associated with PFTs, and it was found that growth and nutritional status of people were associated with changes in FEV 1 . Thus, it was suggested that nutritional interventions might slow the impaired pulmonary function in CF.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…13 Significant associations were identified between nutritional status and PFTs in some studies. 12 In a multicenter study conducted by Zemel et al,14 z-scores of weight and height of people with CF were positively associated with PFTs, and it was found that growth and nutritional status of people were associated with changes in FEV 1 . Thus, it was suggested that nutritional interventions might slow the impaired pulmonary function in CF.…”
Section: Discussionmentioning
confidence: 97%
“…Management of nutrition, which is a risk factor for morbidity and mortality is important in people with CF as lung function, pulmonary muscle function, and exercise tolerance are associated with nutritional status 11,12 . Although many physicians consider malnutrition as a result of lung disease, it is a contributing factor to lung disease 12 . In some studies, nutritional status has been associated with survival for people with CF, and stabilization has been observed in malnourished people when their nutritional status improves 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several additional studies also reported associations between imbalanced iron status and other inflammatory lung diseases. Thus, there is evidence that iron deficiency increases airway inflammation and leads to worse lung function in patients with lung cancer, 33 chronic obstructive pulmonary disease, 34 thalassemia, 35 and cystic fibrosis 36 . However, studies of the association of iron deficiency with childhood airway dysfunction have yielded disparate results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is evidence that iron deficiency increases airway inflammation and leads to worse lung function in patients with lung cancer, 33 chronic obstructive pulmonary disease, 34 thalassemia, 35 and cystic fibrosis. 36 However, studies of the association of iron deficiency with childhood airway dysfunction have yielded disparate results. A previous study of adults found that impaired iron stores were associated with worse lung function as indicated by spirometry, but none of the indices of iron were associated with FeNO.…”
Section: Discussionmentioning
confidence: 99%